Robust extrapolation in discrete systems with random jump parameters and incomplete information - Smagin, Valery I. (Applied methods of statistical analysis. Statistical computation and simulation : proceedings of the international workshop, 18-20 September 2019)
An algorithm for the synthesis of a robust extrapolator is considered, which determines the estimate of the state vector of a discrete linear system with random jump parameters described by a Markov chain with a finite number of states under incomplete information about the model and the observation channel. The transfer matrix of the extrapolator are invited to choose independent of the state of the jump process using the nonparametric smoothing procedure.